(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: In slum area there is a very high prevalence of malnutrition. Many factors can cause malnutrition, most of which relate to immunization, socio economic condition and repeated infections, particularly in underprivileged population. Objectives: To observe the nutritional status and effect of immunization and socio economic condition on malnutrition among under-5 children in a selected slum of Dhaka city. Methods: This cross sectional study was conducted among 384 under-5 children randomly selected from PWD slum in Dhaka city. It was carried out during January- 2013 to December-2014. Anthropometric measurements like wasting was determined from weight for height Z-score, stunting was determined from height for age Z-score, underweight was determined from weight for age Z-score and malnutrition also assessed by Mid Upper Arm Circumference (MUAC). Data were analyzed using SPSS version 21. Results: In this study in slum 40.36% were found malnourished according to MUAC, according to weight for height Z-score wasting was present in 29.43% children, according to height for age Z-score stunting was found in 28.39% and according to weight for age Z-score underweight was found in 46.89% children. There is a decreased number of malnutrition cases when family income rise. Out of the 384 study children 68% were completely immunized, 16.9% were incompletely immunized and rest 15.1% were not immunized. Number of MUAC malnutrition, wasting, stunting and underweight cases increases in cases of incomplete immunization and no immunization. Conclusions: Overall, nutritional status of the under-5 child of slum of PWD is not satisfactory. Family income and immunization status plays role in malnutrition. So socioeconomic condition should improve and mass immunization programshould be implemented in urban slum areas. DS (Child) H J 2020; 36(1) : 34-38